2021
DOI: 10.1364/oe.417191
|View full text |Cite
|
Sign up to set email alerts
|

Study of fundamental wave depletion in intracavity second harmonic generation

Abstract: In this paper, a novel approach to modelling intracavity second harmonic generation (SHG) in periodically poled MgO-doped lithium niobate (PPLN) is presented and verified against experimental results. This approach involves combining the coupled nonlinear wave equations with a rate equation model for a diode-pumped solid-state Nd:YVO4 laser, taking into account both the depletion of the fundamental wave due to the energy conversion from the fundamental wave to the SHG wave and the reduction of the fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Despite these drawbacks, the overall logarithmic trend and the relatively good agreement of the theoretical prediction with the experimental trend shows that these effects are not major effects that must be considered with our laser. While the model would most certainly be improved by adding modeling for multiple modes and Gaussian propagation, this work and the work in [32] show that reasonably close results can be obtained for the maximum SHG power using a simplified single mode model that requires significantly less computational power. Additionally, the lack of wavelength selection device in our laser can be attributed to our target application, which is low-cost, compact, watt-level lasers that can be manufactured easily.…”
Section: Maximum Shg Power Vs Ppln Lengthmentioning
confidence: 61%
See 3 more Smart Citations
“…Despite these drawbacks, the overall logarithmic trend and the relatively good agreement of the theoretical prediction with the experimental trend shows that these effects are not major effects that must be considered with our laser. While the model would most certainly be improved by adding modeling for multiple modes and Gaussian propagation, this work and the work in [32] show that reasonably close results can be obtained for the maximum SHG power using a simplified single mode model that requires significantly less computational power. Additionally, the lack of wavelength selection device in our laser can be attributed to our target application, which is low-cost, compact, watt-level lasers that can be manufactured easily.…”
Section: Maximum Shg Power Vs Ppln Lengthmentioning
confidence: 61%
“…This figure presents the simulated results for maximum SHG power (y-axis) versus MgO:PPLN length (x-axis) for an 808 nm pump power of 2, 3, 4 and 5 W (solid lines). The simulation was developed in-house by our research group and has been reported in a previous publication [32]. While the model is described in full detail in the cited publication, we will briefly summarize the model here.…”
Section: Maximum Shg Power Vs Ppln Lengthmentioning
confidence: 99%
See 2 more Smart Citations
“…For a list of the typical loss values and other simulation parameters used in the intracavity model, please refer to Ref. 32 . The circulating fundamental power inside the cavity was measured experimentally by performing the reverse operating, where the measured leaking power was used alongside the transmission of the OC to estimate the intracavity power.…”
Section: Resultsmentioning
confidence: 99%